Sources of value co-destruction : Uber customer perspectives - Sthapit, Erose; Björk, Peter (Emerald, 2019)
Purpose – This study aims to explore the antecedents that generate value co-destruction, the negative outcomes resulting from interactive value formation, in the sharing economy context, particularly taxi services. The focus of the study is on customers’ Uber reviews that are written in English and posted online. Three keywords, ‘‘bad’’, ‘‘terrible’’ and ‘‘awful’’, were used to capture online narratives linked to customers’ negative experiences with Uber. Out of the 758 online reviews, 75 negative reviews were analysed in this study. Design/methodology/approach – A grounded theory approach was used for data analysis. Findings – Two distinct themes resulted in value co-destruction: Uber drivers’ bad behaviour and poor customer service. The managerial implications include that Uber clearly should invest more resources to minimise the negative experiences of its customers by clearly defining the taxi drivers’ tasks and responsibilities. In addition, when customers report their dissatisfaction, they should be dealt with promptly and effectively through good customer service. Research limitations/implications – First, the netnography study, by its nature, was restricted to those customers who shared their reviews online. The study did not consider those customers who have not posted their reviews online. Second, the focus of the study was on customer reviews that were written in English. Third, only three keywords (‘‘bad’’, ‘‘terrible’’ and ‘‘awful’’) were used in the data selection process, limiting the number of review posts (75) that were analysed in this study. In addition, even if this study does not produce statistically generalizable findings, the findings are valuable in an analytical sense. Practical implications – From a managerial perspective, Uber clearly should invest more in resources to minimise the negative experiences of its customers (both domestic customers and tourists) by clearly defining the taxi drivers’ tasks and responsibilities. If the drivers’ tasks are unclear, then customers cannot be served in an effective manner and with consistent service quality. The taxi drivers, regardless of their full-time or part-time work shifts, should ensure that quality services are offered to customers. Providing high-quality service might reduce the number of complaints and result in positive comments and compliments. Originality/value – This study addresses the gap in previous literature by examining customers’ negative experiences during the overall service encounter and antecedents of value co-destruction in the context of Uber. This study contributes to a better understanding of value co-destruction within the sharing economy.
Keywords: transportation; value co-destruction; sharing economy; Uber; interactive value formation; customers; value creation; sharing economy; customer service; enterprises; services; value (properties); business; manners and customs; customer relationship management; fi=Markkinointi|en=Marketing|